The Influence of Subjective Perceptions and the Efficacy of Objective Evaluation in Soccer School Players' Classification: A Cross-Sectional Study - Federico Abate Daga; Franco Veglio; Gian Maria Cherasco; Samuel Agostino (MDPI AG, 2023)
Objectives: The first objective was to investigate the influence of subjective perceptions and the efficacy of objective evaluation regarding the classification of soccer school players by their level of performance. The second objective was to advise on accurate collocation according to objective assessment of players' performance. Methods: An objective evaluation of the players' motor performance abilities and coaches' subjective perceptions of the players' levels of performance was conducted with 34 young football players (U11) from Torino FC soccer school. The players were allocated to three groups based on their perceived performance level at the start of the season. The players were evaluated using a field test battery, and team coaches provided subjective ratings of the players' abilities. Results: MANOVA showed significant differences between the playing levels (F = 2.185, p < 0.05; partial η2 = 0.34) in the 10 × 5 shuttle run, 20 m sprint test (objective evaluations), heading, understanding of the game, positioning on the field, speed and agility (subjective perception) (F = 1.951, p < 0.05; partial η2 = 0.43). A discriminant analysis of the field test scores revealed that 76.5% of players were correctly categorised in one of the three performance-level groups. However, the first group (the best players) had the lowest predictive accuracy rate (58.3%). By comparison, the second group (the average players) had a much higher predictive accuracy rate (83.3%), and the third (the weakest players) had the highest (90.0%). Conclusions: These findings support the role of objective performance evaluation in categorising players of different skill in soccer schools.